Application of segmentation, targeting and positioning at PT Nusadana Capital Indonesia - Filamena Rachma Rachim (Institute of Accounting Research and Novation (IARN), 2021)
This research aims to know whether the positioning that is being clamed by the company matched the customer's perceptions, identify the company's efforts to form positioning, and formulate some efforts that could strengthen the company's positioning in the customer's mind. The data used in this research are as follows; company profile, market profile, and customer opinions. Those data were analyzed by related theories. The sources of the data in this research are the company's equity sales person (Securities Trading Intermediary Representative), customers, and several of literatures. The method used in this research is comparison between the research's results with the related theories. The results of this research show that the company had only partially implemented Kotler's segmentation theory, the company had chosen its target for equity product